2020
DOI: 10.3389/fneur.2020.514136
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of Cortical Sources of Resting State Delta Electroencephalographic Rhythms Are Related to Epileptiform Activity in Patients With Amnesic Mild Cognitive Impairment Not Due to Alzheimer's Disease

Abstract: Babiloni et al. Epileptiform EEG Activity in noADMCI activities discriminated individuals of the two NoADMCI groups with an accuracy of about 70%. The significant percentage of noADMCI-EEA patients showing EEA and marked abnormalities in temporal rsEEG rhythms at delta frequencies suggest a substantial role of underlying neural hypersynchronization mechanisms in their brain dysfunctions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 74 publications
(113 reference statements)
0
11
0
Order By: Relevance
“…Studies by other researchers ( Nayak et al, 2004 ; Koessler et al, 2015 ) also pointed out that mTL spikes or seizures might be detected by quantitative EEG signatures though they are invisible on a scalp EEG. Babiloni et al (2020) found that higher temporal delta source activities are more strongly associated with clinical seizures in AD by estimating regional EEG cortical sources using exact low-resolution brain electromagnetic tomography (eLORETA) freeware. They used the area under receiver operating characteristic (AUROC) curves to index the accuracy of eLORETA solutions in identifying seizures and found an accuracy of 69% ( Babiloni et al, 2020 ).…”
Section: Computational Approachesmentioning
confidence: 99%
“…Studies by other researchers ( Nayak et al, 2004 ; Koessler et al, 2015 ) also pointed out that mTL spikes or seizures might be detected by quantitative EEG signatures though they are invisible on a scalp EEG. Babiloni et al (2020) found that higher temporal delta source activities are more strongly associated with clinical seizures in AD by estimating regional EEG cortical sources using exact low-resolution brain electromagnetic tomography (eLORETA) freeware. They used the area under receiver operating characteristic (AUROC) curves to index the accuracy of eLORETA solutions in identifying seizures and found an accuracy of 69% ( Babiloni et al, 2020 ).…”
Section: Computational Approachesmentioning
confidence: 99%
“…The most common pattern of results reports EEG slowing in MCI compared with healthy aging in middle-high frequencies, typically characterized by a reduction in spectral power in the alpha band [25][26][27][28][29][30][31]. Furthermore, increases in delta and theta power have also been reported [28,[32][33][34][35]]. As a typical example, Babiloni et al [30] statistically tested for differences in the power spectra in a matched group of individuals with MCI and healthy controls, finding an overall decrease in posterior brain alpha power in MCI and increase in parietal delta power in MCI relative to controls.…”
Section: Resting-statementioning
confidence: 99%
“…In the report of Brunetti et al ( 19 ), dedicated software was used for spike detection after which discharges were manually revised. The most complex reporting protocol was applied in the study of Babiloni et al ( 22 ) based on two current reference guidelines ( 26 , 27 ). SEA needed to fulfill at least four of the following six criteria: (1) Di- or triphasic waves with sharp or spiky morphology; (2) different wave durations from the ongoing background activity, either shorter or longer; (3) asymmetry of the waveform: a sharply rising ascending phase and a more slowly decaying descending phase or vice versa; (4) transient component of SEA followed by an associated slow after wave; (5) background EEG activity surrounding SEA disrupted by the presence of the SEA; and (6) distribution of the negative and positive EEG potentials on the scalp suggesting a focal source of the signal in the cortex, corresponding to a radial, oblique, or tangential orientation of the (dipole) source.…”
Section: Introductionmentioning
confidence: 99%
“…The SEA positive and negative groups are compared with neuropsychology only in a few studies with different test batteries. No differences were reported with the Mini-Mental State Examination (MMSE) ( 9 , 13 , 21 , 22 ) and with the Clinical Dementia Rating Scale (CDR) ( 21 ). However, patients with SEA had significantly lower scores on memory measured with the Addenbrooke Cognitive Examination (ACE) in the recent study of Horvath et al ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation